Preoperative anxiety and its impact on surgical outcomes: A systematic review and meta-analysis - Mohamed A. Shebl; Eman Toraih; Menna Shebl; Ahmed Mosaad Tolba; Parisa Ahmed; Harshdeep Singh Banga; Mohab Orz; Mahmoud Tammam; Keroles Saadalla; Mohamed Elsayed; Mennatallah Kamal; Mohamed Abdulla; et al. (Journal of Clinical and Translational Science, 2025)
Abstract